A Different Tenor: Glimpses and Critical Reflections: The Toronto School of Theology at Forty: A Rear-View Mirror Glimpse, Moving Forward: Toronto Journal of Theology: Vol 26, No 1 - Khan, Abrahim H. (Toronto journal of theology, 2010)
On October 19, 2009, the Toronto School of Theology marked its fortieth anniversary with a luncheon. Reflecting on the speeches at the occasion, the Toronto Journal of Theology extended in a challenging and amicable way an invitation to provide more information on how exactly each of the founding member colleges entered into the collaborative endeavour known simply as tst. Brochures and website information on tst are general and sparse in details on its founding and development. By extending the invitation, we wanted each college to tells its story of how it became part of tst, who would have been the primary player(s) in the member institution, and what were the influences and challenges that added to the impetus in forging the arrangement we have today. From each college we invited a senior faculty member who would have had a hand in the move or was in some other way closely connected to or knowledgeable about it. An outsider's critical-evaluative overview of tst would not only be truly a view from a distance, but would obviate having to identify the first among equals in the arrangement, and well suited as a contribution in the set of narratives. With that in mind, we also invited Professor Richard J. Mouw to ponder tst at forty—whither and why?